Serratia Marcescens outbreak on a general pediatric ward in Benin - AHOYO, THEODORA ANGÈLE; BABA MOUSSA, Faride; ADEOTI, MANSOUR; BABA MOUSSA, Lamine (My University, 2012)
Background Serratia marcescens. : Increasing reports in the literature document the existence of nosocomial transmission of The consequences of infections associated to this bacterium can be severe, so it was important to establish strategies for prevention. This study aimed to provide the prevalence of this bacterium in a hospital environment and to examine the main factors increasing the risk of cross contamination. Methods: Various specimen obtained from 790 hospitalized children aged from 0 to 7 years were examined and 940 others samples taken from hands of medical personnel, and various hospital surfaces were also screened for Serratia marcescens presence. Susceptibilities to antimicrobial agents were tested by the disk diffusion method according to NCCLS guidelines. Aggressive infection control measures were instituted. Results: About 123 (38%) patients were infected by Serratia marcescens, including septicaemia 65 (52.85%), 31 (25.2%) urinary tract infections, 12 (9.75%) pneumonia and 15 (12.2%) others infections. From hospital environment, 108/940 (11.50%) isolates were obtained. Antimicrobial susceptibility testing revealed that 56% of strains displaying multi resistance. Infected patients were cohorted and placed on contact precautions. Investigation by the infection control team revealed that the distributors of antiseptic were the main path of Serratia marcescens dissemination. Conclusions: A substantial proportion of cases appeared to be of medical devices origin. New infection control policies and engineering plans were initiated on the basis of our results. Antimicrobial resistance is particularly harmful to infectious disease management in low-income countries since expensive second-line drugs are not readily available.
Keywords: Benin; Nosocomial infection; prevention; pediatrics unit; Serratia marcescens.